Anesthetic Management of a Newborn with a Gastrointestinal Tract Malformation - Oromovich, Unaboev Jasur; Arsenovna, Xamperova Rozanna (American Journal of Biomedicine and Pharmacy, 2025)
Anesthetic management of newborns with gastrointestinal tract anomalies is a complex and highly specialized process that requires consideration of the physiological characteristics of infants, as well as pathophysiological changes caused by congenital pathology. Such anomalies are often accompanied by malnutrition, dehydration, electrolyte imbalance, and a decline in general condition, which significantly complicates the management of anesthesia. Careful preoperative preparation is necessary, including correction of acid-base balance, blood volume, and electrolytes. During surgery, reliable ventilation and hemodynamic control are required using modern anesthetics and real-time monitoring. The postoperative period is also critical, as newborns may experience complications related to respiratory failure and pain, requiring specialized intensive care. This article discusses modern approaches and recommendations for anesthetic management of such patients, emphasizing the importance of interdisciplinary collaboration to improve the safety and quality of medical care